2015
DOI: 10.1186/s12893-015-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, complications and survival after upper abdominal surgery: a prospective cohort study

Abstract: BackgroundPreoperative weight loss and abnormal serum-albumin have traditionally been associated with reduced survival. More recently, a correlation between postoperative complications and reduced long-term survival has been reported and the significance of the relative proportion of skeletal muscle, visceral and subcutaneous adipose tissue has been examined with conflicting results. We investigated how preoperative body composition and major non-fatal complications related to overall survival and compared thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
2
35
0
4
Order By: Relevance
“…11 In a similar study it was stated that serum albumin <3.5g/dl was associated with poor prognosis following abdominal surgery. 12 In the present study the morbidity was increased from 07 (5.5%) to 50 (45.5%).…”
Section: Discussionmentioning
confidence: 68%
“…11 In a similar study it was stated that serum albumin <3.5g/dl was associated with poor prognosis following abdominal surgery. 12 In the present study the morbidity was increased from 07 (5.5%) to 50 (45.5%).…”
Section: Discussionmentioning
confidence: 68%
“…Both the central and peripheral types of obesity carries increased risk of some diseases including diabetes mellitus, hypertension, arthritis, coronary heart disease and surgical complications. 14 It is shown from the study that the wound complications occur relatively more commonly in patients with obesity. Obesity can affect the surgical outcome directly or indirectly being the cause of the systemic disorders.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the prevalence of muscle depletion in the initial sample of 77 patients was described as 33.8% by MMI and 64.1% by PTA, with poor agreement between the methods. A study by Aahlin et al also assessed the prevalence of sarcopenia classified by two different cutoff points, and found variations in these rates. CT images of 157 patients who underwent surgery of the upper gastrointestinal tract and hepatobiliopancreatic tract were evaluated using the sliceOmatic software and MMI calculation was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Using the cutoff point that was also used in this study for MMI, they found a prevalence of sarcopenia in 45.9% of the sample. When performing the classification according to the values proposed by Mourtzakis this index was 70.1% …”
Section: Discussionmentioning
confidence: 99%